Long-term quiescent fibroblast cells transit into senescence. - Shiva Marthandan; Steffen Priebe; Peter Hemmerich; Karolin Klement; Stephan Diekmann (PLoS ONE)
Cellular senescence is described to be a consequence of telomere erosion during the replicative life span of primary human cells. Quiescence should therefore not contribute to cellular aging but rather extend lifespan. Here we tested this hypothesis and demonstrate that cultured long-term quiescent human fibroblasts transit into senescence due to similar cellular mechanisms with similar dynamics and with a similar maximum life span as proliferating controls, even under physiological oxygen conditions. Both, long-term quiescent and senescent fibroblasts almost completely fail to undergo apoptosis. The transition of long-term quiescent fibroblasts into senescence is also independent of HES1 which protects short-term quiescent cells from becoming senescent. Most significantly, DNA damage accumulates during senescence as well as during long-term quiescence at physiological oxygen levels. We suggest that telomere-independent, potentially maintenance driven gradual induction of cellular senescence during quiescence is a counterbalance to tumor development.